Android apps for absolute beginners : - Jackson, Wallace (For professionals by professionals, 2017)
Get your first Android apps up and running with the help of plain English and practical examples. If you have a great idea for an Android app, but have never programmed before, then this book is for you. "Android apps for absolute beginners" cuts through the fog of jargon and mystery that surrounds Android app development, and gives you simple, step-by-step instructions to get you started.